MCM4 Is a Novel Biomarker Associated With Genomic Instability, BRCAness Phenotype, and Therapeutic Potentials in Soft-Tissue Sarcoma - Liu, Qi; Bao, Qiyuan; Xu, Yiqi; Fu, Yucheng; Jin, Zhijian; Wang, Jun; Zhang, Weibin; Shen, Yuhui (Frontiers in Cell and Developmental Biology, 2021)
Soft-tissue sarcoma (STS) is represented by a heterogeneous group of rare malignancies with various molecular oncogenesis. Therapies targeting DNA repair pathways in STS have achieved minimal progress, potentially due to the lack of molecular biomarker(s) beyond the histology subtype. In this report, we comprehensively analyzed the expression profiles of 100 liposarcoma (LPS), the most common STS subtype, in comparison with 21 adipose tissues from multiple GEO datasets to identify the potential prognostic and therapeutic biomarker for LPS. Furthermore, we investigated the TCGA database, our archived tumor samples and patient-derived tumor cell cultures (PTCC) as a validation. We identified a total of 69 common differentially expressed genes (DEGs) among public datasets, with mini-chromosome maintenance protein 4 (MCM4) identified as a novel biomarker correlated with patients’ clinical staging and survival outcome. MCM4-high expression LPS was characterized by MCM4 copy number increase, genomic instability and BRCAness phenotype compared to the MCM4-low expression counterpart. In contrast, the mutational and the immune landscape were minimally different between the two groups. Interestingly, the association of MCM4-high expression with genomic instability and BRCAness were not only validated in LPS samples from our institution (n=66), but also could be expanded to the pan-sarcoma cohort from TCGA database (n=263). Surprisingly, based on 4 sarcoma cell lines and 8 PTCCs (3 LPS and 5 other sarcoma), we demonstrated that MCM4 overexpression tumors were therapeutically sensitive to PARP inhibitor (PARPi) and platinum chemotherapy, independent of the histology subtypes. Our study, for the first time, suggested that MCM4 might be a novel prognostic biomarker, associated with dysregulated DNA repair pathways and potential therapeutic vulnerability in STS.